PERBEDAAN HASIL VISUM ET REPERTUM DALAM SATU OBJEK TERHADAP PEMBUKTIAN PIDANA (PUTUSAN NOMOR 796/PID.B/2022/PN.JKT.SEL): Differences Of Visum Et Repertum In One Object Regarding Evidence Of Criminal (Decision Number 796/Pid.B/2022/Pn.Jkt.Sel) - Muhammad Rayhan Adevan; Gandes Candra Kirana (Faculty of Law, Universitas Trisakti, 2025)
In 2022, a criminal case involving the murder of Brigadier Yosua Hutabarat by Ferdy Sambo was brought before the court. In its ruling Decision Number 796/Pid.B/2022/PN Jkt. South Jakarta District Court found Ferdy Sambo guilty, basing the verdict on written evidence and expert testimony, including a visum et repertum, which was treated both as documentary evidence and expert opinion. The core issue examined in this study is whether the judges legal reasoning particularly in evaluating two differing visum et repertum reports concerning the same object aligns with prevailing legal standards, and whether basing the decision on only one of the reports adheres to legal requirements. The research adopts a normative legal method, relying on secondary data comprising primary and secondary legal sources. Data analysis is qualitative, with conclusions drawn through deductive reasoning. The study concludes that inconsistencies exist between the judge’s decision and the applicable legal framework, especially concerning the evaluation of evidence. According to Article 183 of the Criminal Procedure Code, a judge may only convict a person if there are at least two valid pieces of evidence and the judge is convinced of the defendant’s guilt.